Advancement in treating osteoporosis with traditional Chinese medicine Liuwei Dihuang pill - Wang, Jing (Frontiers in Musculoskeletal Disorders, 2025)
Osteoporosis is becoming a prevalent disorder in the aging society, and its treatment remains challenging. The traditional Chinese medicine (TCM) Liuwei Dihuang pill (LWDHP) is widely used in treating multiple types of diseases including osteoporosis and is receiving increasing attention. Recent experimental and clinical studies have shown that LWDHP can effectively prevent and improve osteoporosis. The therapeutic mechanism of LWDHP is complicated, including the balance between osteoclasts and osteoblasts, anti-inflammation, and modulation of kinase pathways. This review summarizes recent studies of LWDHP in treating osteoporosis. Following the elucidation of its mechanism and the establishment of a modern scientific standard, LWDHP will be a promising therapeutic approach for treating osteoporosis although there is still a long way.